Analisis Pengaruh Suhu dan Tekanan pada Cargo Heater Terhadap Kecepatan Aliran pada Bongkar Muat LPG di Kapal Pertamina Gas 2 - Fazlih, Muhammad Fharhan; Haryanto, Tri; Nurdiansari, Henna; Sitepu, Firdaus (Nama Jurnal Akmi, 2025)
This study examines the effect of temperature and pressure at the cargo heater on the flow rate of LPG during the discharge and loading process on the LPG tanker ship. The main problem is the freezing of LPG (propane and butane) in cold climates which hinders the smooth flow and slows down the discharge and loading process. The research objective is to analyze the effectiveness of heating through cargo heater in reducing the viscosity of LPG and to identify the dominant factors that affect the flow speed. The method used is causal quantitative with multiple linear regression analysis, supported by direct observation data during the discharge and loading process and data processing through statistical software. The results showed that pressure partially had a significant effect on increasing flow rate, while temperature showed no significant effect partially. However, temperature and pressure variables were simultaneously shown to increase LPG flow rate. The conclusion of the study states that proper pressure regulation with adequate temperature support is the key to the efficiency of the discharge and loading process. The implication of the research is the optimization of cargo heater design based on pressure regulation to improve operational performance on gas tankers.